Effect of Milling Parameters on the Surface Roughness of SiCp/Al Materials - Wang, Liang; Pan, Yongqiang; Zhu, Xiaoxin (Manufacturing Technology Journal, 2023)
The presence of reinforcing particles SiCp seriously affects the cutting surface quality of SiCp/Al materials.In this study, different machining parameters were tested to obtain good surface quality, and the surface quality of SiCp/Al alloy material under different milling parameters was studied by using the surface profilometer and scanning electron microscope to explore the effect of cutting pa-rameters on surface quality. The results showed that the Surface roughness value increased with the increase of feed rate and milling speed, and milling speed was the dominant factor in the microstruc-ture evolution of the machined surface. In addition, an exponential model related to feed rate and milling speed was constructed.
Keywords: SiCp/Al; Cutting Parameters; Surface Roughness; Parameter Optimization